ECOWAS Protocol Implementation on Free Movement of Persons and Trade between Nigeria and Benin Republic: An Overview (Journal of Management and Social Sciences, 2020)
The ECOWAS protocol on free movement of persons and trade is inevitable within the African sub-region since no nation is an island; there is necessity for these sovereign nations within the West African sub-continent to interact together in terms of trade, security, and good governance which requires the free movement of persons across the borderline. However, reverse is the case as the implementation of the protocol was not properly implemented by the leaders of the two (2) countries. Consequently, this study examined the extent at which Nigeria and Benin Republic have not complied with the implementation of the ECOWAS protocol on free movement of persons and trade and investigated the level of challenges that hindered the effective implementation of the ECOWAS protocol along Nigeria and Benin Republic on the borderline. The study adopted the qualitative and quantitative methodology for analysis of data collected in respect of the stated objective and the study discovered the following: only the first phase of the ECOWAS protocol was well implemented but others experienced failure in the process of implementation of the protocol, such as trade, and illicit movement. The study recommends that ECOWAS needs to lobby member states to comply with the implementation of the treaty signed on protocols.  Keywords    ECOWAS protocol, free movement persons, free movement of trade, migration and socio-economic development